Oscillation Behavior of a Class of Second-Order Dynamic Equations with Damping on Time Scales - Weisong Chen; Zhenlai Han; Shurong Sun; Tongxing Li (Discrete Dynamics in Nature and Society)
By using a Riccati transformation and inequality, we present some new oscillation theorems for the second-order nonlinear dynamic equation with damping on time scales. An example illustrating the importance of our results is also included.